FEDERAL CLOUD SECURITY: A STRATEGIC APPROACH TO FEDRAMP COMPLIANCE AND GOVERNANCE - Venkata Jagadeesh Reddy Kopparthi, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
Cloud governance in the public sector has become increasingly critical as government agencies accelerate their digital transformation initiatives. This article examines the evolving landscape of secured cloud governance, explicitly focusing on AWS Cloud Services and FedRAMP compliance requirements in public sector implementations. The intersection of cloud governance frameworks with federal security explores how AWS's FedRAMP-compliant solutions address the unique challenges that government agencies face. Modern cloud governance strategies can effectively balance security, compliance, and innovation by examining technical implementations, operational considerations, and real-world applications in healthcare and other public sector domains. The highlight of emerging trends in automation, zero-trust architectures, and multi-cloud governance provides practical recommendations for stakeholders navigating the complex requirements of public sector cloud adoption. This article contributes to the growing knowledge of secure cloud governance and offers valuable insights for agencies seeking to optimize their cloud infrastructure while maintaining stringent compliance standards.